Peran Dakwah Digital dalam Menanamkan Kesadaran Beragama bagi Remaja Generasi Z - Muhammad Alfito Deanoza H; Nindya Alya Ramiza U; Nasywa Annisi Lillah; Abdul Fadhil (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
In the era of globalization, the internet and social media play an important role in many ways. The rise of various social media platforms has paved the way for preachers to preach virtually, with target audiences such as Generation Z teenagers. The purpose of this study is to examine the role of digital da'wah in shaping religious understanding and awareness for Generation Z teenagers. Digital da'wah, which involves platforms such as YouTube, Instagram, TikTok, and Spotify, is the main channel in spreading religious messages to Generation Z teenagers. This research uses a qualitative method with a case study approach and in-depth interviews with Generation Z teenagers who actively access social media. The results showed that digital da'wah plays a major role in improving adolescents' religious understanding, providing easy access to religious materials, and shaping positive behavior in accordance with Islamic values. However, challenges such as content that is not in accordance with religious teachings, as well as the influence of social media that can affect the mindset of teenagers, also need attention.